2020
DOI: 10.1002/evl3.191
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and introgression between toads with different sex chromosome systems

Abstract: The growing interest in the lability of sex determination in non‐model vertebrates such as amphibians and fishes has revealed high rates of sex chromosome turnovers among closely related species of the same clade. Can such lineages hybridize and admix with different sex‐determining systems, or could the changes have precipitated their speciation? We addressed these questions in incipient species of toads (Bufonidae), where we identified a heterogametic transition and characterized their hybrid zone with genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 64 publications
(92 reference statements)
4
29
0
Order By: Relevance
“…The novel sex markers developed in our study confirmed that Hungarian populations of the common toad are female heterogametic, echoing recent findings from Switzerland (Dufresnes et al, 2020). Identification of the common toad's sex chromosomes remained unresolved so far (Dufresnes et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The novel sex markers developed in our study confirmed that Hungarian populations of the common toad are female heterogametic, echoing recent findings from Switzerland (Dufresnes et al, 2020). Identification of the common toad's sex chromosomes remained unresolved so far (Dufresnes et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…The novel sex markers developed in our study confirmed that Hungarian populations of the common toad are female heterogametic, echoing recent findings from Switzerland (Dufresnes et al, 2020). Identification of the common toad's sex chromosomes remained unresolved so far (Dufresnes et al, 2020). Genome BLAST showed that at least three of the four new sex markers are located on different scaffolds, but specific position of these scaffolds is unknown, except for one which is located on chromosome 5.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, hybridization events during post‐glacial range expansions have left traces of introgression over extensive geographical areas (Wielstra & Arntzen, 2012; Wielstra, Burke, Butlin, Avcı, et al., 2017). Hybrid zones often move (Buggs, 2007; Wielstra, 2019), as the parental species shifted distributions since the initial contact, and foreign alleles may persist hundreds of kilometres away from the current transitions (Dufresnes, Litvinchuk, et al., 2020; Wielstra, Burke, Butlin, & Arntzen, 2017). At the regional level, geographical or ecological changes altering population connectivity, such as large river displacements or human‐induced habitat disturbances, can further contribute to dynamically promote or disrupt species boundaries over short time‐scales (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We recently highlighted this matter when re‐investigating European amphibian hybrid zones with hundreds of SNPs obtained from RAD‐sequencing data, which yielded drastically different results compared to previous surveys based on conventional markers (e.g. Dufresnes, Nicieza, et al., 2020; Dufresnes, Litvinchuk, et al., 2020). Therefore, targeting replicate transects with multilocus datasets representative of the entire genome appears necessary to fully grasp the outcome of secondary contacts between hybridizing species (Harrison & Larson, 2016).…”
Section: Introductionmentioning
confidence: 99%